Evaluasi keragaman genetik tanaman Evaluation of Genetic Variances of Bali Cicih Tombong a Local Variety of Corn under Monoculture and Intercropping Systems - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
This research was conducted at the Agricultural Training, Research, and Development Station Gadjah Mada University, Kalitirto Village, District of Berbah, Sleman Regency. It aimed to estimate the genetic variance and heritabilities. The Design I (North Carolina I/NC I) by Comstock-Robinson was used in this research. There were 64 plants random selected as males, to produce 256 full-sib combinations. A nested randomized complete block design was used to evaluate of progenies, on two cropping systems with two replications in the field. The 64 male groups were assigned at random to 8 sets. Each set, therefore, contained 8 half-sib families or 32 full-sib families. At each cropping system the progenies were arranged in replications within sets. Total of full-sib families on two cropping systems, for all replications were 1024 families. The result showed that in general interaction between genotypes and cropping systems were not significant. The genetic variances observed were additive, and no dominance effect. Any traits as number of ears per plant, 100-kernel weight, grain yield per plant and plant height, showed that additive variances on intercropping system higher than monoculture system. Moderate to high values of heritabilities (h2 = 0.376 to 0.602) were found in this study. The average yield of corn was 85.32 g/plant, or about 4.266 ton hat at population about 50000 plants hat. Correlations between grain yield and any traits are significant, and selection of any traits particularly of yield components could improve grain yield. The local corn variety of Bali Cicih Tombong could be developed to a high yield open pollinated variety or synthetic variety. The breeding programs could be done on intercropping system, and multilocation test should be conducted.